(3GdbUjOI GdYjfjIs - (3YHO GdcQje Hf EHQGgje Hf YHO GdcQje GdLjdj GdUhaj , bWH GdOjf,J (B832 (3g` s ((3YdjNGf Hf eUWai s)
(3ChdgG (B:s
(3aDGO Hg TeS GdeMHI SGWY hdjS dfLe GdYPd ajg ehGbY s
(3BNQgG (B:s
(3dh cGf jecffi GdQbGO dMbbJg eTbI CVYa YHGO Gddg YdjNGf MGeOkG ddg JYGdi Ydi fYeg heUdjkG Ydi NjQ Ndbg eMeO hBdg hUMHg CLeYjf JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B50 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B313s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs